Khamar in the presfektip of islamic law - Andi Tamaruddin (Indonesia Prime, 2019)
Islam as a religion and the right for fourteen centuries ago, has warned even prohibiting Muslims from consuming liquor because by consuming these drinks, someone is potentially drunk, so reason can no longer be enabled to think and can ruin the health of oneself and can disturb others. The consequences of such activities, as the same as ones ignored and the will of his passions. Khamar is a potentially intoxicating liqueur made from fruits such as grapes, dates, wheat seeds, wheat, honey, corn, including all kinds of fruits that can be processed.